Influence of Institutional Ownership, Audit Tenure, Leverage, and Company Size on Earnings Persistence in Consumer Goods Industry - Valeny Valeny; Evelyn Kangga; Dianty Putri Purba; Rebecca Evadine (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze the impact of institutional ownership, audit tenure, leverage, and company size on earnings persistence in companies within the consumer goods industry. The independent variables in this study include institutional ownership, audit tenure, leverage, and company size, while the dependent variable is earnings persistence. The research method employed is quantitative research with a population and sample of 74 companies, selected using purposive sampling method, with a sample size of 57 companies. Data analysis used in this study is multiple linear regression analysis processed by using SPSS version 26. The results of the research showed that audit tenure, leverage, and company size have a positive and significant influence on earnings persistence, Institutional ownership has a negative and insignificant influence on earnings persistence. These findings provide a better understanding for company managers, regulators, and investors about the factors influencing earnings persistence in the consumer goods industry. Implications of this research include the importance of managing institutional ownership and audit tenure to enhance earnings stability, as well as considering company size in financial management strategies.